2015
DOI: 10.1109/tdmr.2015.2408211
|View full text |Cite
|
Sign up to set email alerts
|

Void-Free Underfill Process With Variable Frequency Microwave for Higher Throughput in Large Flip Chip Package Application

Abstract: Moisture voiding in underfill materials can cause reliability issues for the flip chip packages. The bake-out step included in the assembly process flow to avoid this problem cannot be completely efficient for some large die size packages. This is due to complex substrate circuit designs and time delays subsequent to the bake-out step. This paper proposes using the variable frequency microwave cure to eliminate the moisture voiding of flip chip large packages assembled without any bake-out step. Results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Macroscopic fracture properties, such as the fracture toughness, adhesion strength and the critical energy release rate at the Si/polymer interface, can be experimentally measured, e.g. via the cantilever beam test [7][8][9]. Although these fracture properties can be applied as input parameters to models to evaluate the reliability of the package, it is still challenging to predict the lifetime of the devices due to the difficulties involved in estimating correctly the local stress or strain levels at some critical positions, such as the die corner, the solder joints and the BEOL.…”
Section: Introductionmentioning
confidence: 99%
“…Macroscopic fracture properties, such as the fracture toughness, adhesion strength and the critical energy release rate at the Si/polymer interface, can be experimentally measured, e.g. via the cantilever beam test [7][8][9]. Although these fracture properties can be applied as input parameters to models to evaluate the reliability of the package, it is still challenging to predict the lifetime of the devices due to the difficulties involved in estimating correctly the local stress or strain levels at some critical positions, such as the die corner, the solder joints and the BEOL.…”
Section: Introductionmentioning
confidence: 99%
“…This technology eliminates the possibility of metal arcing found in single frequency systems. With these uniform VFM fields, it has been reported that polymerization of epoxy thermosets, thermoplastic films, and other polymer systems have been cured at temperatures well below the standard thermal cure, with high extent of cure. In addition, there is evidence of modified thermomechanical properties in these systems, including modulus, crosslink density, stress, and coefficient of thermal expansion .…”
Section: Introductionmentioning
confidence: 99%